Temporomandibular joint (TMJ) disc position in patients with TMJ pain assessed by coronal MRI - Eberhard, Lydia; Giannakopoulos, Nikolaos Nikitas; Rohde, Stefan; Schmitter, Marc (Dentomaxillofacial radiology, 2013)
Objectives:To assess the position of the temporomandibular joint (TMJ) disc in patients with TMJ pain and compare it with equivalent published data of asymptomatic volunteers.Methods:The oblique coronal closed- and open-jaw MR images from 66 patients with TMJ pain were evaluated. Clinical examination followed the research diagnostic criteria for temporomandibular disorders. In all coronal images, the transverse condylar axis and the medial and lateral edges of the disc were determined using special software. Inter-rater agreement was calculated [two raters; inter-rater correlation coefficient (ICC)]. The presence of osteoarthrosis (OA) was determined by two independent raters. The influence of OA was estimated in patients (generalized estimation equation model). The results were compared with those of healthy volunteers (t-test). Differences between closed and open jaw in patients were analysed with the Wilcoxon matched-pair test.Results:The ICC was good for the transverse condylar axis (0.987) and the medial edge of the disc (0.799) and fair for the lateral edge (0.355). On average, the disc projected 5.5% to the medial side; laterally, the condyle was partially uncovered by the disc (−16.6%). In the open-jaw position, both the medial and the lateral edges shifted medially (to 17.6% vs −23.6%, Wilcoxon matched-pair test, p < 0.001). OA had no significant influence (generalized estimation equation model, p = 0.952). The disc position differed significantly from asymptomatic individuals (t-test, p < 0.001) who showed a medial disc position and full coverage of the condyle.Conclusions:In patients with TMJ pain, the disc seems to be smaller and located less medially than in healthy volunteers. The extent of the medial shift on opening was similar.